2017
DOI: 10.1111/acel.12679
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3 deregulation is linked to mitochondrial dysfunction in Alzheimer's disease

Abstract: SummaryAlzheimer's disease (AD) is the leading cause of dementia in the elderly. Despite decades of study, effective treatments for AD are lacking. Mitochondrial dysfunction has been closely linked to the pathogenesis of AD, but the relationship between mitochondrial pathology and neuronal damage is poorly understood. Sirtuins (SIRT, silent mating type information regulation 2 homolog in yeast) are NAD‐dependent histone deacetylases involved in aging and longevity. The objective of this study was to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
118
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(125 citation statements)
references
References 56 publications
3
118
2
2
Order By: Relevance
“…Most recently, overexpression of SIRT3 was demonstrated to prevent αsyn-induced neurodegeneration in a rodent AAV model (Gleave et al, 2017). In humans, down downregulation of SIRT3 has been previously reported in post-mortem human Alzheimer disease brain (Han et al, 2014; Lee et al, 2018).…”
Section: Discussionmentioning
confidence: 86%
“…Most recently, overexpression of SIRT3 was demonstrated to prevent αsyn-induced neurodegeneration in a rodent AAV model (Gleave et al, 2017). In humans, down downregulation of SIRT3 has been previously reported in post-mortem human Alzheimer disease brain (Han et al, 2014; Lee et al, 2018).…”
Section: Discussionmentioning
confidence: 86%
“…[ 22 ] Previous study indicated that SIRT3 activation could lower Aβ and Tau accumulation in the brain of AD mice, playing a neuroprotective role in reducing oxidative neurotoxicity. [ 23,24 ] Activation of SIRT3 could mediate hippocampal synaptic adaptations and ameliorate cognitive deficits in APP mutant mice. [ 25 ] Moreover, SIRT3 deficiency could induce brain mitochondrial dysfunction, microgliosis and elevate NLRP3 inflammasomes and IL‐1β expression, which exacerbated cognitive decline in calorie‐rich western diet induced mice.…”
Section: Discussionmentioning
confidence: 99%
“…As well known, in physiological condition deacetylated p53 prevents DNA damage and mitochondrial dysfunctions, but Alzheimer's patients exhibit a decrease of Sirt3 which is associated to an accumulation of acetylated p53 in the mitochondria of frontal cortex neurons. In this context, the direct deacetylation of mitochondrial p53 on lysine 320 by Sirt3 had neuroprotective effect on Alzheimer's disease slowing its progression [103].…”
Section: Sirtuins In Neurodegenerative Disorders Of Interest For Rehamentioning
confidence: 99%